Consumers’ behavior to purchase fresh agriculture products in the e-commerce platform in Indonesia - Larasati, Ami Retno; Isaskar, Riyanti; Maulidah, Silvana (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2024)
E-commerce is one of the digital marketing systems. It has increased rapidly in 2020 when the COVID-19 pandemic spread. However, there are several obstacles experienced by consumers from online sales, especially when selling fresh agricultural products, such as quality, suitability of products, services, and so on. This research aims to reveal consumer purchasing intentions and purchasing decisions for fresh agricultural products marketed online using the C-TAM-TPB theory. This theory is known to explain online purchases better. This research uses descriptive analysis. Data was obtained through surveys and literature studies on e-commerce fresh agricultural products. The results show that the majority characteristics of online consumers fresh agricultural products on the TukangSayur.co e-commerce are women. Their ages ranges from 26-35 years, and diploma/bachelor level education. There are 3 types of online consumers of fresh agricultural products. The most significant potential for purchasing decisions is type A. Majority of consumers are type A. Type A has a positive attitude towards purchasing. Consumers have confidence and trust in products and services. Through Type A, e-commerce can get more customers because they can provide positive recommendations to other people.JEL Classification L81; M31; Q02To cite this article: Larasati, A. R., Isaskar, R., & Maulidah, S. (2024). Consumers’ behavior to purchase fresh agriculture products in the e-commerce platform in Indonesia. Journal of Socioeconomics and Development, 7(1), 38-51. https://doi.org/10.31328/jsed.v7i1.5216